Advances in accounting education teaching and curriculum innovations. Vol. 4 - Ketz, J. Edward; Schwartz, Bill N.; Emerald eBooks (Bingley, U.K. : Emerald, 2002)
A refereed, academic research annual whose purpose is to meet the needs of individuals interested in ways to improve their classroom instruction. Articles may be either empirical or non-empirical. They emphasize pedagogy, for example, explaining how teaching methods or curricula/programmes can be improved.
A service-learning approach to achieving taxpayer compliance in Alaskan native communities / Robert C. Maloney -- A note on equivalent units calculations : teaching steps vs. teaching concepts / Austin Reitenga -- Teaching accounting information systems using personal computer movies / Judith K. Welch -- Measuring the problem-defining ability of accounting students / Richard E. Baker -- Budgeting for snow removal costs using Monte Carlo simulation : a classroom project / Roberta M. Lipsig -- An exploratory study of student beliefs in the response reliability of teaching evaluation instruments / Michael Harkness -- Using the Wall Street Journal and the internet to implement the AECC'S introductory accounting recommendations / Phillip R. Olds -- Developing intermediate accounting students' analytical and communication skills through the annual report project / Mary York Christ -- Expanding the global market : a case study for evaluating alternatives / Ernest R. Larkins -- Development of teaching skills in doctoral programs vs. faculty performance evaluation : a survey study / Daniel Braswell.
Keywords: Business & Economics -- Accounting -- General; Science -- History; Teaching skills & techniques; Accounting; Accounting -- Study and teaching; Electronic books